The effects of white-popinac on regenerating seasonal semideciduous forests propagate across spatial scales - Zardetto, Juliano [UNESP]; Siqueira, Tadeu [UNESP] (Springer Nature, 2024)
Biological invasions are complex scale-dependent processes. Metacommunity ecology provides the means to understand the effects of invasive species (IS) because it explicitly considers how local and regional processes interact to drive the three main components of biodiversity: alpha, beta, and gamma. White-popinac (Leucaena leucocephala (Lam.) de Wit) is a widely distributed IS in regenerating forests in the Atlantic Forest (Brazil). White-popinac establishment results in a particular spatial occupancy as the species forms dense and homogeneous patches, instead of spreading individuals throughout invaded areas. Here we took advantage of this unique spatial configuration formed by fragments of native forest and their respective regenerating areas, partially occupied by patches of white-popinac, to investigate how local and regional dynamics of plant metacommunities and communities under natural regeneration are affected by white-popinac. We conducted replicated multi-strata surveys in 131 communities distributed among 29 metacommunities of regenerating forests that had different ages of white-popinac invasion. We found (i) Mirrored responses among local and regional scales: at both scales, native species richness decreased with the increase of invasion age, whereas IS richness increased; and (ii) β-diversity of native species decreased with the increase of invasion age, showing that time-advance of invasion led to a homogenizing effect. We also found evidence that the advance of white-popinac patches towards regenerating forests increases with time and proximity to the forest fragment, which likely had indirect effects on regenerating communities by reducing the size of the regenerating area. Our results indicate that the effects of white-popinac invasions on regenerating forests can be so vigorous that they propagate from the local to the regional scale, via a decrease in β-diversity. We reinforce the importance of considering multiscale approaches on assessing effects of white-popinac invasions.
Keywords: Alien species; Biotic indirect effects; Metacommunities; Natural regeneration; Upscaling; White-popinac